The Oil Spill at La Pampilla Refinery and its Effects on the Coastal Marine Ecosystem and in the Local Economy of the Ancon District (Lima, Peru) - Velásquez Cokche, Aaron Rodrigo (2023)
This article reviews what happened with the oil spill at La Pampilla refinery and the negative impacts it caused to the coastal marine ecosystem and to artisanal fishermen and residents who live from tourism and local gastronomy in the Ancon district; as well as the strategies implemented by the private sector and by the Peruvian government to date, to manage such negative externalities affecting the environment and said stakeholders. Based on this review, some proposals for action are presented, which will remain for discussion or as contributions, for  remeasurthe damaged ecosystem, and reactivatng artisanal fishing and the local economy in the short, medium and long term in the Ancon district.